Effect of aging on metabolic status and hormone responsiveness in the ovary - Elrmly, Mustafa Ali, author; Barisas, B. George, advisor; Roess, Deborah A., advisor; Crans, Debbie C., committee member; Carnevale, Elaine, committee member (Colorado State University. Libraries, 2019)
There were significant effects of mares' ages on gene expression in granolosa cells. Most of the effects we noted were on the expression of AMPK subunits, italics indicating genes rather than gene protein products, although there were significant effects of animal age on GLUT4 and IGF-1R expression as well. In general, increased expression of selected AMPK subunits occurred in older animals and, with one exception, in cells pre-treated with medium that did not contain FBS or additional glucose. Although the underlying cause of increased expression of the AMPK subunits was not determined in this study, various cellular stresses such as nutritional deprevation can lead to AMPK activation. This may be sufficient in aging animals to drive an increase in AMPK subunit expression. In addition to AMPK effects, there was a decrease in IGF-1R expression in older animals although this occurred only in cells pre-treated with medium containing FBS and additional glucose. There was also decreased expression of GLUT4 following hCG treatment and, again, this occurred only when cells were pre-treated with FBS and additional glucose. We then evaluated membrane lipid order to determine whether animal age affects the membrane structure of granulosa cells. Membrane lipid structure including formation of raft microdomains may affect signaling by receptors involved in reproductive and metabolic functions. Insulin receptors, IGF-1 receptors and EGF receptors require highly ordered membrane microdomains for signal transduction. In general, plasma membranes from older animals had more ordered membranes, perhaps due to an increase in in vivo cholesterol synthesis with age. Finally, we examined hormone responsiveness of granulosa cells from young and old mares fed a normal hay-based diet or antioxidant-enhanced commericial diet to evaluate hormone responsiveness with aging. Mares fed an enhanced antioxidant-rich diet showed increased insulin responsiveness, which suggests that at least some effects of aging, namely reduced insulin responses can be treated with an improved diet.